2012
DOI: 10.1515/jpm-2012-0080
|View full text |Cite
|
Sign up to set email alerts
|

Does docosahexaenoic acid (DHA) status in pregnancy have any impact on postnatal growth? Six-year follow-up of a prospective randomized double-blind monocenter study on low-dose DHA supplements

Abstract: Fetuses and breastfed children depend on the maternal docosahexaenoic acid (DHA) supply, which might have long-lasting consequences. We studied the growth of 6-year-old children whose mothers received supplemental DHA from midpregnancy to 3 months after delivery. One hundred and forty-four pregnant women had been randomized to receive one of three vitamin-mineral supplements, one supplying an additional 200 mg/day DHA. Of the original sample, 120 children were measured at age 6 years with standardized methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 45 publications
3
30
0
Order By: Relevance
“…We did not find a sustained difference in the BMI z-score between the offspring of mothers who received high dose n-3 supplementation versus a placebo in the primary analysis by randomization group, but we did find a significant association in the exploratory analysis taking into account breastfeeding and measured DHA levels. The negative finding by randomization group is largely consistent with the literature, where there are now multiple clinical trials which have found no effect of DHA supplementation on standard measures of childhood adiposity [16,20,21]. While there is heterogeneity in the enrollment criteria among these studies (e.g., normal weight women enrolled) and the dosage of DHA, the finding of a lack of an effect on progeny outcomes is mostly consistent, though there are notable exceptions [22].…”
Section: Discussionsupporting
confidence: 84%
“…We did not find a sustained difference in the BMI z-score between the offspring of mothers who received high dose n-3 supplementation versus a placebo in the primary analysis by randomization group, but we did find a significant association in the exploratory analysis taking into account breastfeeding and measured DHA levels. The negative finding by randomization group is largely consistent with the literature, where there are now multiple clinical trials which have found no effect of DHA supplementation on standard measures of childhood adiposity [16,20,21]. While there is heterogeneity in the enrollment criteria among these studies (e.g., normal weight women enrolled) and the dosage of DHA, the finding of a lack of an effect on progeny outcomes is mostly consistent, though there are notable exceptions [22].…”
Section: Discussionsupporting
confidence: 84%
“…Potential explanations for the discrepancy between our findings and previous studies include differences in the dose and type of n-3 LCPUFA supplied, the timing of the supplementation, the trial design, and the accuracy of measurements. The dose of n-3 LCPUFA in our trial was 2.4 g per day, which is higher than in most previous studies, in which 900 mg or 1.5 g was administered,792526 and the high number of participants increased the statistical power to detect effects on growth and body composition compared with previous studies 27. One other trial supplemented with a dose similar to ours from week 30 of pregnancy and completed follow-up for 243 participants at age 19 years, finding no effect on waist circumference or BMI, which could be caused by low numbers 28.…”
Section: Discussionmentioning
confidence: 59%
“…Animal studies suggest that the qualitative composition of PUFA may influence adipose tissue development . Variation in circulating PUFA levels has been associated to variation in body composition in pre‐pubertal children, with n‐6 and n‐3 PUFA having opposite effects on adiposity ; however, this association has so far not been explored in newborns. Here, we studied whether body composition in early infancy relates to PUFA levels in the maternal or fetal circulation at birth.…”
Section: Introductionmentioning
confidence: 99%